P415 Improving food-related quality of life in Inflammatory Bowel Disease with a novel web-based intervention: a randomised controlled feasibility trial. (21st January 2022) - Cox, S; Wall, C; Clarke, H; Drysdale, C; Czuber-Dochan, W; Lomer, M; Lindsay, J; Whelan, K
Abstract: Background: Food-related quality of life (FR-QoL) refers to the psychosocial aspects and pleasure derived from food, eating and drinking. Impaired FR-QoL is prevalent in inflammatory bowel disease (IBD) and is associated with reduced intakes of fibre and certain micronutrients. Patient and health professional focus groups identified the need for web-based support and education on food in IBD, which was subsequently developed through experience-based co-design. The aim of this study was to establish the feasibility of a randomised controlled trial (RCT) investigating the effectiveness of the web-based intervention compared to usual care on FR-QoL in people with newly diagnosed IBD. Methods: A randomised controlled feasibility trial was conducted in adults with Crohn's disease or ulcerative colitis diagnosed in the preceding, 12 months. Patients with active and inactive IBD experiencing impaired FR-QoL (≤90 scored on the validated FR-QoL-29 questionnaire) were recruited. Participants were delivered usual care by their IBD team and were also randomised to either access to the web-based intervention (containing information and patient and clinician videos on various IBD-specific food and nutrition considerations) or no access to the website for, 12 weeks. Questionnaires were completed at baseline and end of trial to assess FR-QoL (FR-QoL-29), health-related quality of life (UK IBDQ), IBD distress (IBD Distress Scale) and anxiety and depression (HADS). Google Analytics was used to investigate usage of the web-based intervention. Results: In total, 50 participants (ITT population) were recruited (81 screened), 30 randomised to the web-based intervention and, 20 to usual care, with, 48 completing the trial (PP population). In the ITT analysis, a greater increase in FR-QoL was observed in the web-based intervention (+11.7 SD, 18.2) than usual care group (+1.4 SD, 20.4, P=0.057), whilst IBD distress reduced in the web-based intervention (-6.8 SD, 26.6) and increased in the usual care group (+8.3 SD, 25.5, P=0.052). Participants in the web-based intervention group logged into the website an average of, 4.2 (SD, 2.9) times, and spent an average of, 13 minutes, 41 seconds (SD, 15 minutes, 1 second) on the website per visit. The most frequently accessed content covered dietary management of specific gut symptoms (accessed by, 52% of participants). In qualitative interviews the participants reported the intervention to be clear, user friendly, easy to navigate, and a good source of educational information. Conclusion: This feasibility study demonstrates that a RCT of a web-based intervention is feasible and potentially effective in improving FR-QoL in IBD. An adequately powered RCT investigating the effectiveness of this intervention in IBD is feasible and now warranted.